Count my lies eaudiobook A gma book club pick!. - Stava, Sophie (Simon & Schuster Audio, 2025)
A GOOD MORNING AMERICA BOOK CLUB PICK "The very definition of a page-turner! This smart, original, twisty story had me gripped from the first to the last page." —Liane Moriarty, New York Times bestselling author A read-in-one-night suspense thriller narrated by a compulsive liar whose little white lies allow her to enter into the life and comfort of a wealthy married couple who are harboring much darker secrets themselves. For the millions of us still chasing those gone girls, this is perfect for fans of Lisa Jewell, Lucy Foley, and Laura Dave. Sloane Caraway is a liar. Harmless lies, mostly, to make her self-proclaimed sad, little life a bit more interesting. So when Sloane sees a young girl in tears at a park one afternoon, she can't help herself—she tells the girl's (very attractive) dad she's a nurse and helps him pull a bee stinger from the girl's foot. With this lie, and chance encounter, Sloane becomes the nanny for the wealthy, and privileged Jay and Violet Lockhart. The perfect New York couple, with a brownstone, a daughter in private school, and summers on Block Island. But maybe Sloane isn't the only one lying, and all that's picture-perfect harbors a much more dangerous truth. To say anything more is to spoil the most exciting, twisty, and bitingly smart suspense novel to come out in years. The thing about lies is that they add up, form their own truth and a twisted prison of a world. And in Count My Lies , Sophie Stava spins a breakneck, unputdownable thriller about the secrets we keep, and the terrifying dangers that lurk just under the images we spend so much time trying to maintain. Careful what you lie for.